(untitled) (Los Angeles, 2015)
Dr. Martin Luther King, Jr.'s historical struggle to secure voting rights for all people. A dangerous and terrifying campaign that culminated with an epic march from Selma to Montgomery, Alabama in 1964.
Keywords: Quyền công dân,Civil rights; Hoa Kỳ,America